2023
DOI: 10.1182/blood.2022015583
|View full text |Cite
|
Sign up to set email alerts
|

How I treat thrombotic microangiopathy in the era of rapid genomics

Abstract: Thrombotic microangiopathy (TMA) encompasses various genetically driven diseases. The emergence of ultra-fast genomic sequencing has recently opened up new avenues of research for genetic investigations in the setting of intensive care units. TMA is likely to be a suitable focus for fast-track genomic sequencing. By establishing an expeditious molecular diagnosis of patients with complement-dependent hemolytic uremic syndrome, fast-track genomic sequencing allows for the timely implementation or withdrawal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Streamlined genotyping of patients may detect pathogenic variants in patients otherwise deemed unlikely to carry the disease based on purely clinical features. 6 In this case, the results suggest that aHUS may go unrecognized or mimic vascular nephropathy as was the case for 5 of the patients, because none of them were suspected to have aHUS, and in some cases despite extensive investigations and a protracted follow-up. 7 Malignant hypertension complicated by TMA has recently been contemplated as a promising application for anti-C5 treatment, irrespective of genetic background.…”
Section: Discussionmentioning
confidence: 55%
“…Streamlined genotyping of patients may detect pathogenic variants in patients otherwise deemed unlikely to carry the disease based on purely clinical features. 6 In this case, the results suggest that aHUS may go unrecognized or mimic vascular nephropathy as was the case for 5 of the patients, because none of them were suspected to have aHUS, and in some cases despite extensive investigations and a protracted follow-up. 7 Malignant hypertension complicated by TMA has recently been contemplated as a promising application for anti-C5 treatment, irrespective of genetic background.…”
Section: Discussionmentioning
confidence: 55%
“…This groundbreaking report raises the hope that rapid‐sequencing‐based diagnosis could be applied to the deciphering of HUS in emergency settings. As a matter of fact, a very recent report from Mesnard et al demonstrated the ability of rapid exome sequencing to reshape the diagnosis and guide highly tailored therapy within a few weeks in patients with TMA 83 . Ultrarapid nanopore genome sequencing can even further shorten the turnaround time, providing genetic testing on a daily timeframe, to guide clinical management in critically ill patients 84 …”
Section: How To Identify Complement‐driven Disease Beyond Atypical Husmentioning
confidence: 99%
“…As endothelial dysfunction remains a clinical challenge 19,20 and is increasingly involved in many complications after alloHCT, it is therefore crucial to develop new tools to easily assess the risk for each patient and to help predict transplantation-related mortality. In this setting, we conducted a retrospective study in order to assess the role of VWF as a potential predictive biomarker of transplant-related endothelial dysfunction and complications after alloHCT.…”
Section: Introductionmentioning
confidence: 99%